Event tourism in Azerbaijan: current state and mechanisms for its improvement in the context of world experience - A. G. Akhundova (Вестник университета)
Event tourism is a dynamically developing sector of the global tourism industry, the share of which increases by 1.5% annually. This segment plays a key role in stimulating the local economy, attracting investment and developing cultural exchange. In Azerbaijan, which has a rich historical and cultural heritage, event tourism has significant potential. However, its development in the regions faces a number of problems that need to be addressed for more efficient use of existing opportunities. This article discusses the current state of event tourism in Azerbaijan, studies certain events held in the republic, substantiates its importance for the socio-economic development of the country’s regions and proposes mechanisms for its improvement based on international experience. The purpose of this article is to analyse the current state of event tourism in Azerbaijan, assess its potential for the socio-economic development of regions and develop recommendations for its improvement, considering existing problems and prospects. The object of the study is to identify problems and explore opportunities related to the development of event tourism in Azerbaijan. The subject of the research is the mechanisms for improving event tourism in the regions of Azerbaijan, including the analysis of current problems, assessment of potential and development of recommendations for improving the accompanying infrastructure, financing, marketing and other key aspects in the context of studying and applying foreign experience. The work uses an analytical research method based on a review of scientific papers in the field of event tourism.